On the economic evaluation of the Stabex system - Roland Herrmann (Intereconomics, 1982)
The discussion on the significance for development policy of the Stabex system, which gained additional impetus as a result of the financing problems observed for the first time in 1981, has up to now suffered from a lack of empirical analysis of the scheme's effects. The following article attempts to quantitatively determine some of these effects for the period 1975–79 and to evaluate the scheme according to aspects of stabilisation, distribution and allocation.
Keywords: 330; Stabex